PENGARUH BOOK TAX DIFFERENCES, ARUS KAS OPERASI, DAN TINGKAT HUTANG TERHADAP PERSISTENSI LABA - Rahmatika Yunita, 13.05.52.0102; Indarti, MG. Kentris (Students' Journal of Accounting and Banking, 2017)
This research test the influence of capital book tax difference based on temporary and permanent differences, operating cash flow, and leverage on the earnings persistence. The research doing in Indonesia Stock Exchange for 3 years using analysis unit manufacturing company. The method sampling using a porposive sampling by period of 2013 to 2015. The analiys technique that used is multiple regression analysis. The results of this research suggerts that tempoeary is negative influence and significant on the earnings persistence. Permanent difference is positive influence and no significant on the earnings persistence. Operating cash flow has possitive and significant effect on earnings persistence, while leverage have negative effects and signifikant on earnings persistence.Keywords: Book Tax Differences, Operating Cash Flow, Leverage, and Earnings Persistence